2014
DOI: 10.1152/ajprenal.00196.2014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular nucleotides from dying cells act as molecular signals to promote wound repair in renal tubular injury

Abstract: Acute kidney injury (AKI) often correlates with poor prognosis and is followed by various severe unfavorable systemic outcomes. It is important to understand the pathophysiology of AKI for the development of novel therapeutic approaches toward promoting renal regeneration after injury. Recent studies have indicated that AKI-induced tubular cell death plays an active role in the onset of tissue regeneration; however, the mechanisms underlying renal tubular repair after injury have yet to be understood. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Wounding MCF-10A cells in the presence of apyrase prevents cells from migrating into the wounded area (Figure 3, B and C). This lack of migration in the presence of apyrase agrees with previous wound studies (Wesley et al , 2007; Gault et al , 2014; Nakagawa et al , 2014; Takada et al , 2014). Overall we find that the initial release of ATP is required for Ca 2+ activation, as well as for epithelial wound closure.…”
Section: Resultssupporting
confidence: 92%
“…Wounding MCF-10A cells in the presence of apyrase prevents cells from migrating into the wounded area (Figure 3, B and C). This lack of migration in the presence of apyrase agrees with previous wound studies (Wesley et al , 2007; Gault et al , 2014; Nakagawa et al , 2014; Takada et al , 2014). Overall we find that the initial release of ATP is required for Ca 2+ activation, as well as for epithelial wound closure.…”
Section: Resultssupporting
confidence: 92%
“…46 ATP infusion had a protective effect on renal regeneration after ischemic insult 47 ; however, it may also function as the source of adenosine. 48 In vitro injury studies by Kribben et al 49 and Nakagawa et al 50 identified ATP as a proregenerative factor in isolated rat PT culture.…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused on the role of α-catenin in regulating cell death since renal tubular epithelium cell death is a hallmark of AKI [23]. Increased apoptosis has been reported in α-catenin deleted mammary glands of mice [24].…”
Section: Discussionmentioning
confidence: 99%